Return from Siberia : a Japanese life in war and peace, 1925-2015 - Oguma, Eiji, 1962-; Noble, David; LTCB International Library Trust; Kokusai Bunka Kaikan (Tokyo, Japan) (Tokyo : International House of Japan, 2018)
What was it like to live through the dizzying changes in Japanese society in the twentieth century, as Japan formed its own imperial colonies in Asia, was defeated in World War II, and achieved its postwar economic miracle? In this book, sociologist Oguma Eiji skillfully locates his father Kenji's personal experiences of this era in the context of concurrent social, economic, and political trends, blending oral history and social history.
Before the army -- In the army -- Siberia -- Political indoctrination -- A hardscrabble life -- The tuberculosis sanatorium -- The postwar economic boom -- Memories of the war -- The wartime compensation lawsuit -- Afterword -- Interview process -- Appendix: filming Father and Me.
Translation of : Ikite kaette kita otoko.
'LTCB International Library Trust/International House of Japan.'
Includes bibliographical references.
Translated into English from original Japanese.
Keywords: Oguma, Kenji, -- 1925-; Soldiers -- Japan -- Biography; Sino-Japanese War, 1937-1945 -- Biography; World War, 1939-1945 -- Prisoners and prisons, Russian; Prisoners of war -- Japan; Japan -- History -- 1945-, -- Biography